APPLICATION OF PARTICIPATORY RURAL APPRAISAL TECHNIQUE IN THE DEVELOPMENT OF SUSTAINABLE AND DISABILITY-FRIENDLY TOURISM DESTINATIONS (STUDY CASE IN SUMBER MARON TOURISM, KARANGSUKO VILLAGE, PAGELARAN) - Rostyawan, Aldy; Amarulloh, Adhitya; Kusmanto, Hari (DEVELOPMENT: Journal of Community Engagement, 2025)
Rural tourism is a widely adopted form of sustainable tourism development, as it has proven effective in addressing contemporary demands. This is evident from efforts to enhance economic well-being, foster community-based tourism potential, and demonstrate active community involvement in regional tourism advancement. This paper aims to showcase the achievements of the Karangsuko Rural Tourism Village community and the Sumber Maron tourism managers, drawing from research and community engagement in the implementation of sustainable tourism development. The study focuses on improving and integrating the three core pillars of sustainable tourism: environmental sustainability, social inclusion, and economic sustainability, to provide economic benefits and support community well-being. The research was conducted in the Karangsuko Rural Tourism Village, Pagelaran District, Malang Regency, utilizing the Participatory Rural Appraisal model or technique, along with in-depth interviews with village residents, government, and tourism managers. The findings indicate that the Sumber Maron Tourism Managers have embraced the concept and objectives of sustainable tourism by developing innovations and leveraging tourism potential through the application of sustainable tourism development in rural areas. This success is demonstrated by increased awareness and commitment to supporting the principles and pillars of sustainable tourism.